Adverse Selection, Commitment, and Renegotiation: Extension to and Evidence from Insurance Markets - Dionne, Georges; Doherty, Neil A. (Journal of Political Economy, 1994)
With asymmetric information, full commitment to long-term contracts may permit markets to approach first-best allocations. However, commitment can be undermined by opportunistic behavior, notably renegotiation. We reexamine commitment in insurance markets. We present an alternative model (which extends Laffont and Tirole's procurement model to address uncertainty and competition), which involves semipooling in the first period followed by separation. This and competing models (e.g., single-period models and no-commitment models) have different predictions concerning temporal patterns of insurer profitability. A test using California data suggests that some automobile insurers use commitment to attract selective portfolios comprising disproportionate numbers of low risks.